A novel double clip-based vascular closure device in antegrade and retrograde femoral punctures: A single-center experience in peripheral non-cardiac procedures. Issue 5 (September 2022) - Thurner, Annette; Heuer, Anjana; Augustin, Anne Marie; Gietzen, Carsten; Bley, Thorsten A; Kickuth, Ralph
Background: This retrospective study investigates the efficacy and safety of the novel Celt ACD ® vascular closure device (VCD) following antegrade and retrograde common femoral artery (CFA) punctures for the treatment of peripheral artery disease in a challenging patient collective (e.g. calcifications, obesity, and anticoagulation). Methods: A total of 208 VCDs (i.e. 100 antegrade and 108 retrograde) were deployed between October 2019 and December 2020 in a tertiary referral interventional radiology department. Fifty-two devices were undersized in relation to the introducer sheath (up to 2 Fr). Technical success and VCD related complications were evaluated in the immediate post procedure period and the following 24 h clinically. In 68% of cases, additional duplex ultrasound was performed prior to discharge. Results: The overall technical success rate was 97%. Technical failures following antegrade approach were due to a too acute access angle (⩾60°), rendering it impossible to pass the applicator tip through the sheath lumen. A subgroup analysis of technical success pinpoints severe calcification as another key limiting factor in VCD use ( p  = 0.004). Comparing equally sized with undersized device selection ( p  = 0.196), direction of approach ( p  = 0.265), and body mass index ( p  = 0.184) proved to be insignificant. Five (2%, 5/208) major complications occurred: Four antegrade (i.e. one false aneurysm, one vessel laceration with retroperitoneal hemorrhage, two device migrations; 4%, 4/100) and one following retrograde access (i.e. >6 cm hematoma, 1%, 1/108)). Complications were successfully managed with manual compression or interventional procedures. Conclusions: The novel clip-based VCD proved to be effective with a low VCD related complication rate.